(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Romeroso RB, Tandang DN, Navarrete IA. 2021. Short Communication: New distributional record of Phyllanthus securinegoides Merr. (Phyllanthaceae) and Rinorea niccolifera Fernando (Violaceae) of Homonhon Island, Philippines. Biodiversitas 22: 501-506. Homonhon Island is an ultramafic forest island located on the east coast of Guiuan, Eastern Samar, Philippines. Due to the naturally rich deposit of Ni and Cr ore, the island is affected by mining activities where metallophytes thrive. These metallophytes have the potential to use in mining industries for ecological restoration. However, metallophytes are least documented in the Philippines. Phyllanthus securinegoides Merr. and Rinorea niccolifera Fernando is some of the metallophytes mostly documented in Surigao, Palawan, and Zambales, Philippines, but are not yet recorded in Samar. Moreover, these metallophytes are considered as new distribution records of metallophytes in the Philippines island. These plant resources must be conserved due to their physiological uniqueness. The study provides photographs and other relevant information of the collected species to compare the previous and present collections based on the previous and available literature.